(3GdUMGaI GdJdaRjhfjI (B/s - (3HhQjJScj s; (3NVhQs ((3OeTb (B:s [(3Ohf fGTQ(B] (3,s, 1990)
(3GdGLGHI GdYdejI h GdeJNUUI GdJj jbOegG gPG GdcJGH Yf gPg GdGSFdI GdVQhQjI ddUMajjf h GdJdaRjhf h GdeHGMKjf GdGYdGejjf h ddOGQSjf GdGYdGejjf GdYQH h Pdc dGfgG JSGge aj JYejb Gdage h JQaY ef eSJhi GdeeGQSI h JhSY GaGb GdeYQaI Ydi GdJdaRjhf cGfge hSjdI GJUGd YQagG GdGfSGfs
Keywords: (3GdJdaRjhfs; (3GdUMGaIs